Effects of dietary Zilpaterol hydrochloride and non-steroidal growth implant on growth and carcass characteristics of feedlot lambs - Webb, E.C. (Edward Cottington) (University of Pretoria, 2015)
Dissertation (MScAgric)--University of Pretoria, 2015.